Managing Multi-Background English Proficiency Levels in University English Classrooms: Challenges and Best Practices - Ellen Juita Gultom (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2026)
The study explores challenges and strategies employed by university English instructors for handling heterogeneous EFIC classrooms. As higher education increasingly admits more diverse groups of students, instructors must serve both low- and high-proficiency learners all in the same classroom. The researchers took a qualitative descriptive approach and data was obtained through semi-structured interviews via Google Form with 8 English lecturers from several universities in Indonesia. Five major challenges were identified through thematic analysis. Five key challenges were identified through thematic analysis: slower progress for the class, difficulty engaging students, variations in student confidence levels, problems with assessment and classroom polarization. Despite these difficulties, instructors utilized varied teaching practices including peer mentoring, small-group work and task support. Most respondents, however, reported limited institutional support and lack of training and resources. The study proposes three other institutional reforms: testing, class grouping policies, access to teaching aides and targeted professional development. These results, The need for structured response to provide uniform and effective language instruction with mixed proficiency levels.